Towarzysze na Targach - Trojanowicz, Roman (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
A rememberance of the Black Thursday events, observed by the author (a student of medicine back then) witnessed as a tourist guide for a group organized by Province Committee of the Polish United Workers’ Party from Bialystok, sightseeing at the Poznań International Fairs.